Trait Mindfulness and Counterproductive Work Behavior: The Role of Stop and Start Control - Endang Parahyanti; Muhammad Rizky (Psympathic: Jurnal Ilmiah Psikologi)
This study aimed to examine the antecedents of Counterproductive Work Behavior (CWB) by investigating two dimensions of self-control, namely stop and start control, as mediators between trait mindfulness and CWB. A correlational research design was employed, and the participants were full-time workers aged between 20 and 39 years. The instruments consisted of the Stop Control and Start Control Scale, Mindfulness Attention Awareness Scale (MAAS), and Counterproductive Work Behavior Checklist (CWB-C). The results of the mediation analysis showed that the trait mindfulness had an indirect effect on CWB through stop control (ab = -.11, p < .01) and start control (ab = -.04, p < .01), as well as a direct effect on CWB (c’ = -.07, p < .01; c’ = -.24, p < .01). These findings suggested that stop and start control partially mediated the relationship between trait mindfulness and CWB.